ANIMATION MULTIMEDIA APPLICATIONS ON THE SURVEY RESULTS MARKETING PT HARMONI GRAHA INDAH using Macromedia FLASH 8.0 - Zaenuddin Achmad (Jurnal Sistem Komputer, 2008)
Animation we often encounter was limited to the entertainment world, but also animation can also be used in other areas. For example in the world of business and commerce. With animation, the delivery to another party will not be boring. Animation applications is expected to help marketing the store to be able to explain the survey results, which can berdasasarkan from the field. In the writing of this research will be discussed how to make an animated multimedia marketing survey Harmony store at PT Graha Indah simple and attractive. This animation created using Macromedia Flash application program 8. Where used Macromedia Flash to create animations in the world of entertainment (entertain).